A) x2 -49 = 0б) 8x + 6x2 = 0B) 4x2 = 36x​

0
0

A) x2 -49 = 0б) 8x + 6×2 = 0B) 4×2 = 36x​

0
0

a)

x2 — 49 = 0

x² —  49 = 0

x² = 49

x = +\sqrt{49}

Ответ: x = 7, -7

b)

8x + 6×2 = 0

8x + 6x² = 0

2x (4 + 3x) = 0

2x (4 + 3x) = 0 на 2

\frac{2x(4+3x)}{2} = \frac{0}{2}

x (4 + 3x) = \frac{0}{2}

x (4 + 3x) = 0

x = 0

4 + 3x = 0

x = 0

x = -\frac{4}{3}

x = 0,-\frac{4}{3}

Ответ: x = 0,-\frac{4}{3}

c)

4×2 = 36

4x² = 36

x² = 36

x = ± \sqrt{9}

Ответ: x = 3, -3

0
0

Объяснение:

а) х²-49=0

х²=49

х=±7

б) 6х²+8х=0

2х(3х-4)=0

2х=0. 3х=4

х1=0. х2=1⅓

в) 4х²=36х

4х²-36х=0

4х(х-9)=х

4х=0. х-9=0

х1=0. х2=9

Показано 2 результата